2016
DOI: 10.5937/zasmat1601156k
|View full text |Cite
|
Sign up to set email alerts
|

New examples of electrodeposited alloy systems with pattern formation

Abstract: The experience in the pattern formation during electrodeposition of alloys is summarized. The possibility of formation of spatio-temporal structures due to the spontaneous co-deposition of different phases and their self-organization in ordered structures is demonstrated in some new not investigated in this aspect alloy systems, like Cu-Sb, Ag-Sn, Pd-In and Au-In.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Before starting the SPEM characterization applying Ar sputtering cycles, the pristine structure of the sample was characterized by OM (Figure 1A) and SEM (Figure 2). Previous relevant studies 3,5,38 have already shown the formation of spatial structures during alloy electrodeposition. These structures can be imaged accurately by OM, but exhibit a surprisingly poor contrast in SEM, confirmed by the present study as well.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Before starting the SPEM characterization applying Ar sputtering cycles, the pristine structure of the sample was characterized by OM (Figure 1A) and SEM (Figure 2). Previous relevant studies 3,5,38 have already shown the formation of spatial structures during alloy electrodeposition. These structures can be imaged accurately by OM, but exhibit a surprisingly poor contrast in SEM, confirmed by the present study as well.…”
Section: Resultsmentioning
confidence: 97%
“…Notwithstanding the relatively vast literature on electrochemical pattern formation, the general problem of correlating the electrodeposited patterns with specific alloy chemistry and plating conditions, as well as issues regarding sensitivity, reproducibility and scalability, have not been faced systematically yet. Recent reviews of experimental results , and parametric mathematical modeling (see section S5 of the Supporting Information) have paved the way of this prospective investigation. In any case, spatial patterns in electrodeposited alloys have recently been shown to correlate with a two-phase structure including an intermetallic (see Bozzini et al and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation